Developing Responsible Tourist Behavior Through Smart Tourism Technology, Cultural Authenticity, and Memorable Tourism Experiences: Evidence From Bali - I Gusti Made Riko Hendrajana; I Made Sudjana; Firlie Lanovia Amir (Sharia Economic and Management Business Journal (SEMBJ), 2026)
Background: The increasing demand for sustainable tourism has highlighted the importance of encouraging responsible tourist behavior while enhancing visitor experiences. This study investigates the effects of Smart Tourism Technology (STT) and Cultural Authenticity (CA) on Responsible Tourist Behavior (RTB), with Memorable Tourism Experience (MTE) serving as a mediating variable. Grounded in the Stimulus–Organism–Response (S-O-R) theory, the study proposes that smart tourism technology and cultural authenticity function as external stimuli that shape tourists' memorable experiences and subsequently influence their behavioral responses. Method: A quantitative explanatory research design was employed, and data were collected from 372 domestic and international tourists who had visited Bali within the previous twelve months. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Results: The findings reveal that Smart Tourism Technology and Cultural Authenticity significantly enhance Memorable Tourism Experience. Furthermore, Smart Tourism Technology, Cultural Authenticity, and Memorable Tourism Experience positively influence Responsible Tourist Behavior. The mediation analysis confirms that Memorable Tourism Experience significantly mediates the relationship between Smart Tourism Technology and Responsible Tourist Behavior, as well as between Cultural Authenticity and Responsible Tourist Behavior. These findings support the application of S-O-R theory in sustainable tourism research and demonstrate that integrating smart tourism technologies with authentic cultural experiences can foster responsible tourist behavior. Conclusion: The study provides theoretical contributions to tourism behavior literature and practical implications for destination managers seeking to promote sustainable tourism development in Bali.